2016
DOI: 10.1038/srep36790
|View full text |Cite
|
Sign up to set email alerts
|

Protein Inhibitor of Activated STAT3 Suppresses Oxidized LDL-induced Cell Responses during Atherosclerosis in Apolipoprotein E-deficient Mice

Abstract: Atherosclerosis is a serious public health concern. Excessive inflammatory responses of vascular cells are considered a pivotal pathogenesis mechanism underlying atherosclerosis development. It is known that Janus kinase/signal transducer and activator of transcription 3 (JAK/STAT3) signalling plays an important role in atherosclerosis progression. Protein inhibitor of activated STAT3 (PIAS3) is the key negative regulator of JAK/STAT3 signalling. However, its effect on atherogenesis is unknown. Here, we observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Moreover, STAT1/STAT3 transcription factors physically interact with the gene promoter region of Nox1 and Nox4 for positive upregulation [52]. In vascular cells and macrophages, either JAK2 inhibitor or STAT1/ STAT3 knockdown blunted Nox activity and expression and subsequently hampered ROS production [52][53][54]. In the context of diabetes, our in vitro results indicate that hyperglycemia and a combination of pro-inflammatory cytokines act on renal, vascular, and phagocytic cells to generate ROS and maintain cell injury, and effect blocked by Nox inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, STAT1/STAT3 transcription factors physically interact with the gene promoter region of Nox1 and Nox4 for positive upregulation [52]. In vascular cells and macrophages, either JAK2 inhibitor or STAT1/ STAT3 knockdown blunted Nox activity and expression and subsequently hampered ROS production [52][53][54]. In the context of diabetes, our in vitro results indicate that hyperglycemia and a combination of pro-inflammatory cytokines act on renal, vascular, and phagocytic cells to generate ROS and maintain cell injury, and effect blocked by Nox inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, MIAT was also found to inhibit ox-LDL-induced apoptosis in HCAMCs partly by inhibition of miR-181b, which induces the upregulation of signal transducer and activator of transcription 3 (STAT3) in vitro (87). Notably, STAT3 is a critical inflammatory mediator in atherosclerosis and inhibition of STAT3 suppressed the ox-LDL induced inflammation in high-fat fed ApoE −/− mice (124). MIAT promotes inflammation and increased lipid content to accelerate atherosclerosis development, however its effect on apoptosis of SMCs needs further study.…”
Section: Miatmentioning
confidence: 99%
“…immunofluorescence-stained sections indicated that 42.66% of all cells in plaques from control animals exhibited activated NFκB signaling, whereas only 22.48% of cells were positive in animals undergoing treatment ( Figure 3C); a 47% reduction. Given the cross talk between NFκB and STAT3 [43][44][45][46] and the crucial role of STAT3 signaling in the progression of atherosclerosis, [47][48][49] STAT3 protein expression in the whole aorta was evaluated ( Figure 3D and E). p5RHH-JNK2 siRNA nanoparticle-treated animals exhibited a 46% reduction in whole-aorta STAT3 expression (P=0.004) compared to controls.…”
Section: Jnk2 Silencing Reduces Inflammatory Signalingmentioning
confidence: 99%